Gut phageome: challenges in research and impact on human microbiota - Yu, Xiao; Cheng, Li; Yi, Xin; Li, Bing; Li, Xueqin; Liu, Xiang; Liu, Zhihong; Kong, Xiaomei (Frontiers in Microbiology, 2024)
The human gut microbiome plays a critical role in maintaining our health. Fluctuations in the diversity and structure of the gut microbiota have been implicated in the pathogenesis of several metabolic and inflammatory conditions. Dietary patterns, medication, smoking, alcohol consumption, and physical activity can all influence the abundance of different types of microbiota in the gut, which in turn can affect the health of individuals. Intestinal phages are an essential component of the gut microbiome, but most studies predominantly focus on the structure and dynamics of gut bacteria while neglecting the role of phages in shaping the gut microbiome. As bacteria-killing viruses, the distribution of bacteriophages in the intestine, their role in influencing the intestinal microbiota, and their mechanisms of action remain elusive. Herein, we present an overview of the current knowledge of gut phages, their lifestyles, identification, and potential impact on the gut microbiota.